Application of Life Cycle Assessment (LCA) in Sugar Industries - Dwi Astuti Arieyanti; Siwi Dwi Astuti Rahayu; Hadiyanto Hadiyanto (E3S Web of Conferences, 2018)
Sugar is one of the main commodities that are needed for human life. The demand of sugar is very high with the trend increase from year to year. This condition makes the sugar industry become a leading industry that must be maintained sustainability. The sustainability of the sugar industry is influenced by the use of energy and natural resources and the resulting environmental impacts. Therefore, an effort is needed to analyze the environmental aspects and potential environmental impacts resulting from a product (sugar), by using Life Cycle Assessment (LCA). LCA is a very important tool for the analysis of a process/system from its cradle to grave. This technique is very useful in the estimation of energy usage and environmental load of a product/system. This paper aims to describe the main elements of sugar industries using Life Cycle Assessment.